2010
DOI: 10.3928/15428877-20100215-34
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Macular Cavernous Hemangioma with Systemic Infliximab

Abstract: Cavernous hemangioma of the retina is an unusual vascular hamartoma that has been reported to occur either sporadically or as a dominantly inherited trait. A case of a large and sporadic macular cavernous hemangioma that was successfully treated with systemic infliximab as a first line of treatment is presented. The patient was referred with decreased vision of the right eye for 6 months. Fundus examination disclosed a reddish elevated lesion in the posterior pole that obscured the macula and encroached on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[ 8 ] Temporary regression of the macular cavernous tumor with visual improvement in response to systemic infliximab infusion (tumor necrosis factor-α antibodies) has been published in recent years. [ 9 ] Compared to these, our case opens up a new arena in treating patients with symptomatic hemangioma of the disc or retina safely with PDT.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Temporary regression of the macular cavernous tumor with visual improvement in response to systemic infliximab infusion (tumor necrosis factor-α antibodies) has been published in recent years. [ 9 ] Compared to these, our case opens up a new arena in treating patients with symptomatic hemangioma of the disc or retina safely with PDT.…”
Section: Discussionmentioning
confidence: 99%
“…They found improvement of visual acuity with a prominent involution of the tumor two weeks after the second infusion of infliximab. [7] Conversely, Alsulaiman et al[8] reported no evident change in the size of the retinal cavernous hemangioma after 4 cycles of intravenous infliximab over a period of 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…[5]However in cases where macula is involved with threat to vision, there is case report with infliximab given intravenously showing visual acuity improving with a marked involution of the tumor in the right eye. [6] Although association of cavernous hemangioma of the retina has been shown with cerebral and other systemic hemangiomas, Patient's life is hardly damaged by complications of cavernous hemangioma of the brain. Because of autosomal dominant transmission all family members, with and without fundus findings, should undergo computed tomography or magnetic resonance imagining of the brain to preclude intracranial vascular anomaly.…”
Section: Discussionmentioning
confidence: 99%